Development and Qualitative Evaluation of A Biomimicry-Enriched Engineering Design-Based Teaching Module on The Sound and Its Properties Unit - Derya Kaltakci-Gurel; Esra Gokce (Universitas Negeri Semarang, 2026)
This study proposes and investigates a biomimicry-enriched, engineering design-based teaching approach for physics. Grounded in situated learning theory, the approach aims to enhance student comprehension and interest by connecting abstract concepts to real-world problem-solving and daily life, a crucial mandate in physics education research. The focus of this research is on the “sound and its properties” unit. The implementation was conducted over 22 class hours, during which students participated in nature-inspired engineering design cycles comprising stages such as problem definition, imagining solutions, identifying sources of inspiration, and modelling. Using a qualitative research design, the study analyzed data from 57 sixth-grade students in Ankara, Türkiye. Qualitative data, collected via students’ cooperative group activity sheets, required students to identify biological sources and map similarities between nature and their designs. These data were analyzed through inductive document and content analysis to categorize typical designs and the specific levels of biomimetic mimicry achieved by the groups. The findings provide detailed insights into the students’ application of physics principles to design nature-inspired engineering solutions related to sound and its properties.